ACSM Call to action statement: COVID-19 considerations for sports and physical activity - Denay, K. L.; Breslow, R. G.; Turner, M. N.; Nieman, D. C.; Roberts, W. O.; Best, T. M. (Current Sports Medicine Reports, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes an infectious disease (COVID-19) that has spread to more than 200 countries and affected more than 6 million people. SARS-CoV-2 is a highly transmissible virus that is primarily spread through airborne droplets when infected individuals congregate with others in enclosed spaces. Based on clinical observations and autopsy data, the virus attacks vascular tissue throughout the body causing ischemic injury and inflammatory reactions that destroy cells and tissues. The virus also causes direct tissue damage, and the body's immune system can "over respond," resulting in a "cytokine storm" capable of significant destruction. We do not know if the virus will express a seasonal variation, like influenza, or be a constant year-round threat. This alone will challenge planning for a variety of events, including personal and group physical activities. Although this call to action focuses on individual fitness and physical activity, team sports are recognized as a vital activity for many. It is important to recognize for those returning to team sports that the risk for COVID-19 transmission may be higher in high-contact sports, such as football and soccer, as compared with low-contact sports, such as baseball and softball. Accordingly, diagnostic testing is likely to become more important in high-risk contact sports and should be adapted based on local guidelines. In summary, activating the general population for the health benefits of physical activity may be challenging as we emerge from COVID-19. Increasing physical activity will require individuals and groups to walk a fine line between benefit and risk. The main vehicle for spread of the virus is airborne droplets from breathing, talking, coughing, and sneezing. Breathing hard appears to increase the amount of airborne virus. Physical activity in groups or spaces where adequate social distancing cannot be maintained will require masking to reduce transmission. For the general public, evidence shows that physical distancing of more than 1 m can be effective and that face masks (disposable or reusable 12- to 16-layer cotton type) are associated with some protection, even in nonhealth care settings. Widespread surveillance testing may be needed to track transmission prior to resuming team sports and contact activities. Athletes and active people cannot be the collateral damage in our quest to achieve herd immunity, and group spectator sports may not return in the short term. Decision making should be driven by scientific data and not competing financial interests.